Perancangan Knowledge Management System Resep Masakan Indonesia Menggunakan Model SECI - Nugraha, Zahra Sabila; Wibowo, Ishma Tsabita; Maulana Asykari Muhammad; Yuni Sugiarti (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Indonesia is rich in diverse traditional culinary heritage, with recipes often passed down orally or as tacit knowledge, making it challenging to preserve and at risk of being lost. This study aims to design a knowledge management system (KMS) for managing, storing, and distributing Indonesian culinary recipes using the SECI model (Socialization, Externalization, Combination, and Internalization). The SECI model was selected for its ability to convert tacit knowledge into explicit knowledge that can be managed and disseminated through information systems. The research method includes needs analysis through literature review, observation, and interviews with culinary community members, along with a design review to understand the characteristics of traditional recipes. The system was developed using JavaScript and the Next.js framework to create a responsive user interface. Testing was conducted using the black-box method to evaluate system performance based on user needs. The results show that the KMS was well-received by users and effectively provided a platform for storing and distributing traditional recipes. This system serves not only as a repository but also as a digital ecosystem supporting the preservation of Indonesian culinary heritage. It is expected that the KMS will be a valuable tool in documenting and disseminating Indonesian culinary knowledge to the wider public, including younger generations and the international community. Further testing is needed to optimize the system for more effective support in preserving Indonesia’s culinary culture.